Transmission of Schistsomiasis in The Blue Nile State, SUDAN, (An investigated study in May 2009 – April 2010) - Taha Ahmed, Mohamed Khalid (Gezira Journal of Health Sciences, 2018)
The present study was carried out at randomly selected villages in the Blue Nile State to assess the transmission of schistosomiasis, the distribution of snails in freshwater canals especially the intermediate host of Schistosoma haematobium , identification of different types of schistosomes and their epidemic. A random sample which represented 25% of the residents in each village in addition to all pupils was enrolled in the study. From each individual a stool sample and a urine sample were subjected to microscopic examination to determine the prevalence and intensity of infection. The examination was repeated one year latter in each enrolled individual. Snails were collected by the standard scooping method small water bodies and canals. The snail’s habitats were critically studied. The collected snails were reared in the laboratory to determine the Schistosoma parasites they harbour.  The relation between people water contact behaviour and prevalence and intensity of infection was assessed. The data was subjected to epidemiology statistical package. The study revealed the absence of intestinal schistosomiasis in the studied villages. The prevalence of infection among the pupils was 13.8% and the intensity was 21.6 egg/10 ml, and among the resident was 12.3% and the intensity was 21.9 egg/10 ml. The levels of urinary schistosomiasis differed significantly ( p < 0.05) between the residents and the pupils. The highest infection rate was recorded in the age group 15-19 years (15.0% and 23.7egg/10ml). The study recorded the presence of the Prosobrancha ( Melanoides tuberculata , L. carinatus and C. bulimoides ) which are of no medical importance and the Pulmonate ( Bulinus truncatus , Bulinus forskalii and Biomphalaria pfeifferi ) of which B. forskalii of no medical importance . The dominated snail was M. tuberculata . The density of all snails dropped during the flood season, except for M. tuberculata which to protect its soft tissues inside the snails by the operculum.  A significant relation (p<0.05) was found between the physical (turbidity and temperature), chemical and biological (decaying matter) characteristics of the water bodies and reproduction of snails. The density of the snails was negatively affected by distance of the site from the point of water entrance into the canal, season, abundance and density of vegetation. The results showed infectivity of B. truncatus in water sites recurrently visited by the people indicating that schistosomiasis is endemic in the area. The infectivity among the studies population varied from light to average but few showed acute infection. Treatment with Praziquantel (under medical supervision) resulted in a significant reduction in the prevalence of S. haematobium infection among school children (50.7%) and villagers (50.4%). The results revealed that the high improper diagnosis associated with the modified KATO diagnostic technique yielded low infection rate especially if only one sample was investigated. Any delay in repeated sampling might decrease or increase infection rate. The results showed that B. truncatus is highly susceptible to S. haematobium infection. The infection rates increased with increasing number of miracidia to which the snail was exposed. Cercariae emergence (began after the 5th week from infection) starts at 6.00 a. m. reaching a peak at 12.00-2.00 and decreases gradually till it stops at sun set. The maximum cercariae output was attained at the 9th week. There was a positive relationship between the number of miracidia the snail is exposed to and the number of cercariae liberated from it and the death among infected snails. The study of human water contact pattern showed a positive correlation between infection indices and swimming, bathing, padding that exposes most of the body parts to cercariae for a long time. It is suggested that the results of this study to be considered when implementing a strategic schistosomiasis combating action in the Blue Nile State. The present study was an attempt to investigate transmission of schistosomiasis in Blue Nile State from May 2009 to April 2010. The influence of some critical micro-epidemiological factors on transmission of schistosomiasis in the State was assessed. The Overall Objective of the present study: Fluctuations in snail population densities have been observed in many parts of the world. These fluctuations have been shown to be associated with variations in temperature and rainfall (Coulibaly and Madsen, 1990).   اجريت هذه الدراسة في قرى اختيرت عشوائيا فى ولاية النيل الأزرق لدراسة إنتقال مرض البلهارسيا، وتوزيع القواقع في قنوات المياه العذبة، خاصة العائل الوسيط لطفيلي المنشقة والتعرف على أنواع البلهارسيا ووبائية مرض المنشقات المعوية والبولية. اختيرت عينة شوائية تمثل  25 % من سكان كل قرية بالإضافة إلى كل التلاميذ وأُجريت لهم الفحوصات الطفيلية المجهرية لتحديد نسبة المرض وشدته. كما أُجرى مسح وبائي آخر بعد عام في ذات العينة المختارة. جمعت القواقع بالمغرفة القياسية من الميعات والمجاري المائية ودرست بيئة تواجدها كما تم تربيتها فى المعمل للتحقق من انواع طفيليات المنشقة. كما درست العلاقة بين عادات وسلوكيات اتصال السكان بالماء ومؤشرات ومعدل الإصابة. تم تحليل النتائج  بواسطة حزمة المعلومات  الوبائية  الإحصائية. بينت النتائج توطن المنشقة البولية وعدم وجود المنشقة المعوية في مناطق الدراسة. نسبة الإصابة بين التلاميذ كانت 13.8% وشدة الإصابة 21.6 بيضة/ 10 مل وبين المواطنين كانت 12.3% وشدتها 21.9 بيضة/ 10 مل. اختلفت مناسيب الإصابة بالمنشقة البولية اختلافاً معنوياً p < 0.05) ) بين السكان والتلاميذ، وبين المجموعات العمرية. أعلى مناسيب الإصابة سجلت في المجموعة العمرية 15-19 سنة (15.0%و 23.7 .بيضة/ 10 مل، على التوالى). أثبتت الدراسة وجود ستة أنواع من القواقع هى: الكليوباترا، الميلانويدس واللانستس من رتبة الخيشوميات وليس لها أهمية طبية. مجموعة رتبة الرئويات شملت البولاينس ترنكاتس والبايومفلاريا و لها أهميتة طبية، والبولاينس فورسكالي وليس له أهمية طبية. الميلانويدس كان هو القوقع السائد. انخفضت كثافة أجناس القواقع فى فترة الخريف عدا جنس الميلانويدس الذى لا يتأثر كثيراً بعكورة بسبب وجود غطاء فتحة الصدفة الذي يحمي الأجهزة الداخلية للحلزون. وجدت علاقة معنوية p < 0.05) ) بين الصفات الفيزيائية (العكورة و الحرارة) والكيميائية والإحيائية (المواد المتحللة) للمجاري والبرك المائية و تكاثر القواقع. اثر بعد الموقع عن مدخل الماء في القناة، الموسم وتوفر وكثافة الأعشاب المائية على كثافة مجموعات القواقع. وضحت البيانات أن البولاينس ترنكاتس مصاب بالطفيل في مواقع الماء التى يتردد عليها السكان مما يؤشر لوبائية وتوطن المرض في المنطقة. تراوحت حدة الإصابة بين السكان بين الخفيفة والمتوسطة بينما عانت قلة من الإصابة الحادة. علاج المصابين بعقار البرازيكوانتيل (تحت اشراف طبى) خفض الإصابة بنسبة 50.7% بين التلاميذ المصابين و 50.4% بين سكان القرى . أبرزت نتائج الدراسة أن نسبة الخطأ العالية في تشخيص الطفيل عبر تقنية  كاتو المعدلة تؤدى  لخفض مؤشرات الإصابة إذا ما فحصت عينة واحدة، كما أن التأخير في  جمع العينات المطلوبة للفحص ولو لأسبوع قد يزيد أو يخفض مؤشرات المرض. أثبتت التجارب المختبرية أن البولاينس ترنكاتس شديدة القابلية  للإصابة بالطفيل وأن نسبة الإصابة  تزداد طردياً بزيادة اعداد الطور المعدي (الميرسيديم) الذي يتعرض له القوقع، وأن الطور  المعدي للإنسان (السركاريا) يبدأ خروجه من القوقع (بعد الأسبوع  الخامس) عند السادسة صباحاً لتصل اعداده للذروة  بين 12 - 2 ظهراً، ثم ينخفض قبل التلاشي التام عند السادسة مساء. ويمثل الأسبوع التاسع قمة إنتاجية السركاريا. ثبت أن العلاقة طردية بين اعداد الميرسيديم التى يتعرض لها  القوقع وبين السركاريا التي تخرج منه وكذلك نسبة الموت وسط القواقع المصابة دراسة نشاطات الأهالي  واتصالهم  بماء  القنوات والميعات وضحت أن  هنالك ارتباطاً  وثيقاً بين مؤشرات الإصابة و ممارسة السباحة، الاستحمام، الخوض في الماء التى تعرض  أكبر جزء من الجسم للماء لمدة طويلة.   توصى الدراسة بأخذ هذه النتائج في الاعتبار عند تطبيق أي إستراتيجية لمكافحة داء المنشقات بولاية النيل الأزرق. الأهداف الرئيسية لهذه الدراسة هي التحقيق والتعرف على العوامل والأسباب التي كانت من وراء إنتقال مرض  البلهارسيا بالولاية ، ولدراسة توزيع حلزونات المياه العذبة في قنوات المياه ، خاصة العائل الوسيط لطفيلي المنشقة. كذلك التعرف على أنواع البلهارسيا في المنطقة. أيضاً من أهداف هذه  الدراسة  هو  إعطاء  صورة  متكاملة  عن  وبائية  مرض  المنشقات  المعوية  والبولية بولاية النيل الأزرق من مايو2009   حتى  أبريل 2010